2002
DOI: 10.1046/j.1365-3024.2002.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of γδ T cells on the CD4+ T cell and antibody response during a primary Plasmodium chabaudi chabaudi infection in mice

Abstract: A primary infection with Plasmodium chabaudi chabaudi (AS) is characterized by an expansion of gammadelta cells after the acute phase of infection in mice. This is particularly marked during chronic infections in B cell-deficient mice. Infections in gammadelta T cell-deficient mice suggest that, although these cells play some role in the control of parasitaemia and can produce interferon-gamma, they do not appear to be involved in the development of hypoglycaemia, loss of weight and temperature during a P. c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…Although the depletion of ␥␦ T cells by MAb treatment had no effect on the number of splenic CD4 ϩ T cells, a significant (P Ͻ 0.005) increase in parasitemia also occurred. However, during acute parasitemia, ␥␦ T cells affect the nature of CD4 ϩ T-cell help, which becomes predominantly Th2 in ␥␦ T-cell-deficient mice rather than Th1 as reported for intact control mice (35).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the depletion of ␥␦ T cells by MAb treatment had no effect on the number of splenic CD4 ϩ T cells, a significant (P Ͻ 0.005) increase in parasitemia also occurred. However, during acute parasitemia, ␥␦ T cells affect the nature of CD4 ϩ T-cell help, which becomes predominantly Th2 in ␥␦ T-cell-deficient mice rather than Th1 as reported for intact control mice (35).…”
Section: Discussionmentioning
confidence: 79%
“…Human ␥␦ T cells stimulated with P. falciparum antigen express both type 1 and type 2 cytokines (9,15 ϩ T-cell differentiation during malaria is to elicit either CMI through type 1 cytokines or antibody-dependent immunity (AMI) through type 2 cytokines (30); both arms of the immune response have been reported to be capable of suppressing the parasitemia of acute P. chabaudi malaria (38,50). Sexias et al (35) reported that the production of type 1-dependent antibody isotypes (IgG2a and IgG2b) to Plasmodium antigens in response to primary P. chabaudi infection exceeds the type 2 dependent IgG1 antibody response. In addition, we observed that both IL-4 and IFN-␥ knockout mice are protected against P. chabaudi challenge after immunization with homologous antigenic constructs, AMA-1 or MSP-1 (2), further questioning the concept that protective antibodies against blood-stage P. chabaudi are IL-4 dependent.…”
Section: Discussionmentioning
confidence: 99%
“…There was partial loss of immunity in the B-cell-KO mice in our model, suggesting that the B-cell response may contribute to the protection observed. However, as B-cell-deficient mice have been shown to have a large expansion of γδ T cells in the Plasmodium chabaudi malaria model [41,42], it is possible that it was this response, rather than antibodies, that contributed to protection. Indeed, sporozoites preincubated with plasma from immunized mice resulted in the same prepatent period as in the control.…”
Section: Discussionmentioning
confidence: 99%
“…Protective immunity, limiting circulating parasite load and preventing severe disease, may develop after several exposures to infection. This immunity is mediated not only by Abs (1), but also by cellular effector mechanisms, including the CD4 and CD8 subsets of ␣␤ T cells (2)(3)(4)(5)(6), ␥␦ T cells (7,8), NKT cells (9 -11), dendritic cells (12), macrophages (13), and NK cells (14,15). Most studies of protective immune responses during malaria have focused on the adaptive immune responses induced by immunization with irradiated sporozoites (16).…”
mentioning
confidence: 99%